Gums exudates of Prosopis spp. located in Ecuador: prebiotic potential in animal feed - Rincón-Acosta, Fernando; Hurtado, Ernesto; Robalino-Briones, Cesar; Aguilar-Camba, Paul (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Fiber-rich plant foods have been tested as prebiotics (adjuvant to the growth and activity of the gut microbiota) in animal production, due to their high inulin and fiber content, in order to reduce the use of antibiotics and microbial resistance. The gummy exudate produced by Acacia senegal is a source of nutritional fiber that has been tested as a prebiotic in animal feed. The objective of this study was to analyze the potential use of novel sources of Prosopis spp. gummy exudates as prebiotics in animals of zootechnical interest based on a systematic literature review in indexed journals of the use of gum-hydrocolloids as an alternative supplement in animal feed. The scientific articles reviewed show the benefits of using the gummy exudate of Acacia senegal as a prebiotic in the production of broilers, turkeys, rabbits, and pigs. The gums obtained from Prosopis spp. present physicochemical and nutritional characteristics analogous to those published for gum arabic. Therefore, based on the bibliographic reports consulted, the gummy exudate obtained from Prosopis spp trees located in Ecuador could present a nutritional profile with excellent fiber content, oligosaccharides, essential minerals, and phenolic compounds, which would enhance its use as a promising prebiotic in animal feed, improving the function of the intestinal barrier, favoring the growth of beneficial microbiota,  significantly reducing the populations of pathogenic bacteria, optimizing animal welfare and production.